Characterization of metal resistance genes carried by waterborne free-living and particle-attached bacteria in the Pearl River Estuary. (15th June 2023) - Xie, Xiuqin; Yuan, Ke; Chen, Xin; Zhao, Zongshan; Huang, Yongshun; Hu, Ligang; Liu, Hongtao; Luan, Tiangang; Chen, Baowei
Abstract: Toxic metals can substantially change the bacterial community and functions thereof in aquatic environments. Herein, metal resistance genes (MRGs) are the core genetic foundation for microbial responses to the threats of toxic metals. In this study, waterborne bacteria collected from the Pearl River Estuary (PRE) were separated into the free-living bacteria (FLB) and particle-attached bacteria (PAB), and analyzed using metagenomic approaches. MRGs were ubiquitous in the PRE water and mainly related to Cu, Cr, Zn, Cd and Hg. The levels of PAB MRGs in the PRE water ranged from 8.11 × 10 9 to 9.93 × 10 12 copies/kg, which were significantly higher than those of the FLB ( p  < 0.01). It could be attributed to a large bacterial population attached on the suspended particulate matters (SPMs), which was evidenced by a significant correlation between the PAB MRGs and 16S rRNA gene levels in the PRE water ( p  < 0.05). Moreover, the total levels of PAB MRGs were also significantly correlated with those of FLB MRGs in the PRE water. The spatial pattern of MRGs of both FLB and PAB exhibited a declining trend from the low reaches of the PR to the PRE and on to the coastal areas, which was closely related to metal pollution degree. MRGs likely carried by plasmids were also enriched on the SPMs with a range from to 3.85 × 10 8 to 3.08 × 10 12 copies/kg. MRG profiles and taxonomic composition of the predicted MRG hosts were significantly different between the FLB and PAB in the PRE water. Our results suggested that FLB and PAB could behave differential response to heavy metals in the aquatic environments from the perspective of MRGs. Graphical abstract: Image 1 Highlights: Both MRGs and those likely carried by plasmids were enriched on the SPMs. MRG profiles were significantly different between the FLB and PAB in the PRE water. The levels of MRGs carried by PAB were significantly correlated with those of the FLB. MRG levels in the PRE water presented positive relationships with metal pollution. Taxonomic composition of PAB MRG hosts was differentiated from that of FLB MRG hosts.